PENDAMPINGAN DAN PENERAPAN MODUL HEALING TOUCH DALAM MENGATASI KECEMASAN PADA PERSALINAN OLEH BIDAN KLINIK/PMB DI KOTA PEKANBARU - YAN SARTIKA; ELLY SUSILAWATI (KRIDA CENDEKIA, 2021)
The purpose of this community service activities is to conduct socialization about the Healing Touch method for midwives and mobilizing them to apply the Healing Touch method as a tool for screening early efforts to detect psychological problems for expectant mother in Independent Midwifery Practice of Pekanbaru in 2020. The method of community service activities is carried out by conducting socialization about the Healing Touch method for midwives followed by monitoring and evaluating the application of Healing Touch method by midwives. The results are the socialization of Healing Touch method for midwives at Klinik Jambu Mawar, PMB Hasna Dewi and Klinik Annisa Medika 2,, followed by the practice of applying the Healing Touch method to expectant mother at the three BPM/Clinic. Based on the results of monitoring and evaluation obtained an enhancement in participants’ knowledge with an average value from 45,7 to 76,6, and the application of the Healing Touch method by midwives for early detection of psychological problems in pregnant women obtained an average value of 81,9. It is recommended for midwives to improve their efforts to detect anxiety in pre-term pregnancy until birth delivery to every expectant mother by using the Healing Touch method both during home visits and when the clients visit service facility.